Odorant Metabolism in Humans - Kornbausch, Nicole; Debong, Marcel; Büttner, Andrea; Heydel, Jean-Marie; Loos, Helene (Angewandte Chemie International Edition, 2022)
Odorants are relatively small molecules which are easily taken up and distributed in the human body. Despite their relevance in everyday life, however, only a limited amount of evidence about their metabolism, pathways, and bioactivities in the human body exists. With this Review, we aim to encourage future interdisciplinary research on the function and mechanisms of the biotransformation of odorants, involving different disciplines such as nutrition, medicine, biochemistry, chemistry, and sensory sciences. Starting with a general overview of the different ways of odorant uptake and enzymes involved in the metabolism of odorants, a more precise description of biotransformation processes and their function in the oral cavity, the nose, the lower respiratory tract (LRT), and the gastrointestinal tract (GIT) is given together with an overview of the different routes of odorant excretion. Finally, perspectives for future research are discussed.
CRIS-Team WoS Importer:2022-08-26